Neuromyelitis optica with unilateral diaphragmatic paralysis. (28th September 2018) - Bennji, Sami; Sagar, Diaeddin; Brey, Naeem; Koegelenberg, Coenraad
Abstract : In this case report, we describe the course of a female patient who is known to have neuromyelitis optica (NMO) and developed left hemiparesis and unilateral diaphragmatic paralysis. She was initially treated with intravenous methylprednisolone 1 g daily for 5 days without improvement. Subsequently, she received five sessions of a plasmapheresis. Her hemiparesis had improved after few days. however, the phrenic nerve palsy remained.